Textile dyes loaded chitosan nanoparticles: Characterization, biocompatibility and staining capacity - Costa, Eduardo M.; Silva, Sara; Veiga, Mariana; Baptista, Patricia; Tavaria, Freni K.; Pintado, Manuela E. (Carbohydrate polymers, 2021)
•Chitosan nanoparticles successfully encapsulated textile dyes.•Nanoencapsulation had an average entrapment percentage 90 % for both dyes.•Nanoencapsulated dyes were not cytotoxic towards HaCat cells.•Nanoencapsulated dyes were capable of dyeing textile fabrics. Textile dyeing is a hazardous and toxic process. While traditionally it has been managed through effluent treatment, new approaches focused upon improving the dyeing process are gaining relevance. In this work, we sought to obtain, for the first time, an eco-friendly chitosan-nanoparticle based textile dyeing method. To that end, yellow everzol and navy blue itosperse loaded chitosan nanoparticles were produced and their capacity to dye textiles and cytotoxicity towards human skin cells were evaluated. The results obtained showed that it was possible to obtain nanoencapsulated dyes through ionic gelation with an average entrapment efficacy above 90 %. Nanoparticles presented a positive surface charge and sizes between 190 and 800 nm with yellow everzol NPs occurring via ionic interactions while navy blue itosperse NPs were formed through hydrogen bonds. Furthermore, the produced dye NPs presented no cytotoxicity towards HaCat cells and presented staining percentages reaching 17.60 % for a viscose/wool blend.